2020
DOI: 10.9734/ajbgmb/2020/v6i230146
|View full text |Cite
|
Sign up to set email alerts
|

Partially Purified 3-Mercaptopyruvate Sulphurtransferase Obtained from the Intestine of Cane Rat (Thryonomys swinderianus) as a Detoxifier of Cyanide

Abstract: Cane rat (Thryonomys swinderianus) is an herbivorous animal which feeds on plant materials, including cassavas that are known to contain cyanogenic glycosides. Cyanide or cyanogenic glycosides are known to be toxic for animal consumption. Therefore, Cane rat must have an inherent mechanism for detoxifying cyanide to be able to survive on its food. Previous works on 3MST have been done on several tissues of cane rats other than the intestine. In this work, we characterized and explored a partially purified 3MST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…It is worthy to note that the yield obtained in this study is more than the ones reported by other researchers who used conventional methods such as ammonium sulphate, ion-exchange chromatography and other chromatographic techniques to purify 3-MST. Sanni et al 26 reported a yield of 10.3% after ion exchange chromatography purification of Cane rat 3-MST.…”
Section: Analysis Of the Responsementioning
confidence: 99%
“…It is worthy to note that the yield obtained in this study is more than the ones reported by other researchers who used conventional methods such as ammonium sulphate, ion-exchange chromatography and other chromatographic techniques to purify 3-MST. Sanni et al 26 reported a yield of 10.3% after ion exchange chromatography purification of Cane rat 3-MST.…”
Section: Analysis Of the Responsementioning
confidence: 99%